UPAYA PENCEHAGAN, PENANGGULANGAN, DAN EDUKASI PERAN MAHASISWA DI MASA PANDEMI COVID-19 DI DESA JAYAMEKAR - Gunardi, Gungun; Andriyani, Rismayanti; Mayangsari, Riri; Amaliah Putri, Neng Shinta; Mumtasya, Fajriani; Fauzan, Muhammad Syahrul; Fadilah, Fairuseva Gina; Mikli, Silvie Tira (Jurnal Pengabdian Kepada Masyarakat Babakti, 2022)
Covid-19 is an infectious disease caused by the SARS-COV2 coronavirus. With the outbreak of the disease, people's behavioral habits changed greatly from usual, requiring following health protocols. This thematic real work lecture conducts student devotion efforts on matters related to the prevention of covid-19 while still carrying out health protocols. The program is to support the government in breaking the covid-19 chain which is most importantly educating the public about the dangers of covid-19 in the new normal era. Real work lectures are carried out in groups directly in the area of Jayamekar Village, Padalarang District of West Bandung. This research aims to find out the role of students as a form of community service in order to develop competence and interaction in socializing in the community. This real-time lecture uses data collection methods, interviews, and documentation. Student roles such as education on how to wash hands properly and correctly, spraying disinfectant, helping the distribution of direct cash assistance provided from the government to underprivileged citizens, gymnastics sports, distribution of masks and handsanitizers and the installation of Covid-19 prevention education sticker banners. The results of the study showed that real distance lectures can be felt by the community. The program has been implemented and received positive response enthusiasm from residents, village officials and the local community.